2017
DOI: 10.1039/c6dt04615k
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated metal chelators as anti-parasitic agents with tunable selectivity

Abstract: Trypanosoma cruzi and Leishmania amazonensis are the causative agents of Chagas' disease and leishmaniasis, respectively. These conditions affect millions of people worldwide, especially in developing countries. As such, there is an urgent need for novel, efficient and cost-effective treatments for these diseases, given the growing resistance and side-effects of current therapies. This work details the synthesis and evaluation of the anti-parasitic activity of novel amino- and iminopyridyl metal chelators, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 55 publications
(60 reference statements)
1
23
0
Order By: Relevance
“…Unfortunately, their equally high toxicity on mammalian 293T embryonic kidney cells and J774.1 macrophages meant that these manganese compounds had low selectivity for Leishmania. 225 The complexes are well tolerated by mammalian macrophage cells. Zn(II) complexes had good activity against the L. amazonensis promastigotes, while Cu(II) complexes were unable to inhibit the proliferation of the promastigotes.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, their equally high toxicity on mammalian 293T embryonic kidney cells and J774.1 macrophages meant that these manganese compounds had low selectivity for Leishmania. 225 The complexes are well tolerated by mammalian macrophage cells. Zn(II) complexes had good activity against the L. amazonensis promastigotes, while Cu(II) complexes were unable to inhibit the proliferation of the promastigotes.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Several modes of action for antileishmanial Zn­(II) complexes have been discussed in the literature: inhibition of enzymes essential for parasite carbohydrate metabolism (Embden–Meyerhof pathway); selective recognition of anionic cell surfaces through electrostatic attraction, and specific coordination of cations with phospholipids in the cell membrane. The zinc-based study was conducted by Reddy et al, who in 2017 reported a series of Cu­(II) and Zn­(II) complexes derived from amino- and iminopyridyl ligands . The complexes are well tolerated by mammalian macrophage cells.…”
Section: Leishmaniasismentioning
confidence: 99%
“…The significant efficacies displayed for the Zn-ITZ complexes against the protozoa and fungi demonstrated that these metal complexes might act as multitarget drugs, where itraconazole inhibits sterol 14-␣ demethylases of the parasitic cytochrome P-450 (38), while zinc (an essential trace element for human survival; it has clinical relevance) could act by modes of action already reported (39,40) or by new ones, which we plan to evaluate in future studies. Thus, we plan to determine in the mechanisms of action in future studies to better understand the contribution of both parts of these new chemical identities.…”
Section: Resultsmentioning
confidence: 99%
“…The cancer cells glucose metabolism can be exploited for targeted therapy [60], and consequently, glycoconjugates of various metal complexes were explicitly designed for selective uptake by cells overexpressing glucose transporters [61][62][63]. Apart cancer-specific treatment [39,[41][42][43][64][65][66][67], alternative utilizations of this type of hybrids, as for example antiparasitic therapy, also received a lot of interest [68][69][70].…”
Section: Figurementioning
confidence: 99%